2000
DOI: 10.1182/blood.v96.12.3872.h8003872_3872_3879
|View full text |Cite
|
Sign up to set email alerts
|

Thymomas alter the T-cell subset composition in the blood: a potential mechanism for thymoma-associated autoimmune disease

Abstract: Thymomas are the only tumors that are proven to generate mature T cells from immature precursors. It is unknown, however, whether intratumorous thymopoiesis has an impact on the peripheral T-cell pool and might thus be related to the high frequency of thymoma-associated myasthenia gravis. This study shows, using fluorescence-activated cell sorting-based analyses and T-cell proliferation assays, that thymopoiesis and T-cell function in thymomas correspond with immunologic alterations in the blood. Specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 32 publications
4
64
0
2
Order By: Relevance
“…Notably, 100% of WHO type A tumours were AIRE − , despite their ‘medullary’ sobriquet 30, perhaps questioning the histogenetic classification into cortical and medullary subtypes. Previous studies implied that generation of inefficiently tolerized T‐cells in thymomas and their subsequent export to the periphery contribute to the pathogenesis of the associated autoimmunity 3–5. Therefore, our second finding was unexpected: despite absence of both AIRE and APS‐1‐target autoantigens from thymomas, the disorders and the organ‐specific autoantibodies typical of AIRE‐deficient APS‐1 patients 1 were very infrequent in thymoma patients.…”
Section: Discussionmentioning
confidence: 68%
“…Notably, 100% of WHO type A tumours were AIRE − , despite their ‘medullary’ sobriquet 30, perhaps questioning the histogenetic classification into cortical and medullary subtypes. Previous studies implied that generation of inefficiently tolerized T‐cells in thymomas and their subsequent export to the periphery contribute to the pathogenesis of the associated autoimmunity 3–5. Therefore, our second finding was unexpected: despite absence of both AIRE and APS‐1‐target autoantigens from thymomas, the disorders and the organ‐specific autoantibodies typical of AIRE‐deficient APS‐1 patients 1 were very infrequent in thymoma patients.…”
Section: Discussionmentioning
confidence: 68%
“…The thymic stromal cells and hormones play a key role in modulating the immune reactions through their effects on T-lymphocyte differentiation of both helper and suppressor/cytotoxic cells. The role of thymic dysfunction has been investigated in both murine models [18] and autoimmune diseases of humans [19]. In SSc, different defects of T lymphocytes have been reported, even if their exact pathogenetic role remains largely obscure, probably due to the small number and the inhomogeneity of patient series investigated [2].…”
Section: Discussionmentioning
confidence: 99%
“…No specific autoantibodies, as detected in myasthenia gravis, have ever been identified in oral LP. CD8 + autoantigen‐specific T cells are increased in the peripheral blood of patients with thymoma 10 . Based on these previous reports, direct injury to keratinocytes by cytotoxic T cells induced by thymoma may explain the relationship between LP and thymoma.…”
Section: Discussionmentioning
confidence: 80%
“…Among human neoplasms, thymomas are the only tumours that are proven to generate mature T cells from immature precursors. It has been reported that intratumoral and peripheral T cell subsets are abnormal 10 . Thus, the mechanisms for autoimmune diseases associated with thymoma can generally be divided into two major groups: direct injury by cytotoxic T cells; and damage by autoantibodies induced by helper T cells.…”
Section: Discussionmentioning
confidence: 99%